Geopolitical threats and sovereign Russia: is the clash of civilizations growing? - Ableev, Sergey R.; Zolkin, Andrey L.; Marchenya, Pavel P. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The authors of the article believe that in the modern world where ideological and political confrontation of civilizations is aggravating it is necessary to provide conceptual grounds of multipolar world and civilization identity defense of Russia. The ability of Russia to meet global challenges of Euro-Atlantic civilization gives the chance to other (non-western) civilizations to preserve their sovereignty. Pro-western liberalism can’t become a constructive value foundation for strategic development of Russian civilization. Russia has to strengthen its Eurasian pole of world influence and defend its civilization sovereignty despite any sanctions and threats of the West.
Keywords: civilization; the West; Euro-Atlantic civilization; Russia; Eurasian civilization; civilizational sovereignty; geopolitics